Toxicity of four pesticides on Orius insidiosus under laboratory conditions - Andorno, Andrea Veronica; Carrizo, Paola Irene; Lopez, Silvia Noemi (Department of Agricultural and Food Sciences, Università di Bologna, 2024)
The predatory bug Orius insidiosus (Say) (Rhynchota Anthocoridae) is marketed in Argentina mainly to control thrips in greenhouse sweet pepper and used along with a recommended pesticide application schedule to simultaneously manage the presence of other pests. The accurate assessment of the compatibility of pesticides with predator activity is key for the success of Integrated Pest Management programs. The susceptibility of O. insidiosus to some common pesticides was investigated in the laboratory. Four pesticides (flubendiamide, cyantraniliprole, indoxacarb and azoxystrobin) were assayed for their effects on the predator. These pesticides were tested at a single rate of application, corresponding to their highest label rate. We tested the effect of these compounds on nymphs and adults of O. insidiosus, from contact with residuals. Mortality was recorded 24 hours after the treatment. This study assessed the lethal and fecundity effects of the pesticides on O. insidiosus which were classified according to the definitions of toxicity given by the International Organization for Biological Control. Flubendiamide and azoxystrobin were categorized as harmless, while cyantraniliprole was slightly harmful and indoxacarb was moderately harmful. Only indoxacarb and cyantraniliprole affected the fecundity of the predatory bug.